093 Sleep and Mood Across the Menstrual Cycle in Young Women. (3rd May 2021) - Shuster, Alessandra; Zhang, Jing; Simon, Katharine; Sattari, Negin; Albinni, Benedetta; Alzueta, Elisabet; Dulai, Teji; de Zambotti, Massimiliano; Baker, Fiona; Mednick, Sara
Abstract: Introduction: Sleep modulates mood, with adequate, good-quality sleep associated with a more positive mood. Additionally, sleep is affected by the menstrual cycle in women, with better self-reported sleep quality during non-menses, compared with pre- and during menses. The present study examines the interaction between self-reported sleep quality and mood across the menses (pre/during menses) and non-menses portion of the menstrual cycle. Methods: 10 female participants (27± 2.96) completed sleep and mood diaries over a two month period, answering questions about their nighttime sleep quality and daily mood, and also marking days of menstruation. Each morning participants indicated on a 7-point scale how their overall sleep quality was the previous night. Then, each evening, participants indicated on a 7-point scale the extent to which they felt specific positive and negative moods throughout the day. Time lag cross-correlation and linear regression models were used to determine directionality of sleep quality and mood, and interaction between sleep quality, menses status, and mood levels. Results: Better sleep quality was associated with better mood, with prior sleep quality predicting mood, but prior mood did not predict sleep (cross-correlation time lag = 0) across menses and non-menses. Additionally, on average women reported higher levels of sleep quality and better mood during the non-menses portion of their cycle. During the non-menses portion, women reported higher levels of positive mood (happy, pleased, and joyful), which were mediated by level of sleep quality. Women also reported lower levels of negative mood (depression, frustration, anxiety, unhappiness, and overwhelmed feelings), which were similarly mediated by level of sleep quality. Conclusion: These findings are consistent with the hypothesis that sleep modulates mood, which fluctuates over the course of a woman's menstrual cycle. Moreover, our data suggest that perceived sleep quality impacts mood, and that the menstrual cycle affects both sleep quality and mood Support (if any): Supported by: RF1AG061355 (Baker/Mednick)